Pre-Service Geography Teachers’ Soft Skills And Teaching Self-Efficacy Beliefs In The University Of Cape Coast - Bentil, Samuel (University of Cape Coast, 2025)
The study examined pre-service Geography teachers’ soft skills and teaching self-efficacy beliefs at the University of Cape Coast. It was based on an explanatory sequential mixed-method design guided by a pragmatist philosophical orientation that underpinned this study. The census method was adopted to involve 200 level 400 pre-service Geography teachers in the quantitative phase, while convenient sampling selected 12 participants for a follow-up focus group discussion. Structured soft skills and teaching self-efficacy questionnaires were adapted and validated to collect quantitative data. A semi-structured focus group protocol was used for the follow-up discussion. Data analysis involved descriptive statistics (frequency, percentages, mean, standard deviation) and inferential statistics (One-way and Two-way MANOVA, PLS-SEM) for quantitative data, and thematic analysis for qualitative data. Results showed that pre-service Geography teachers possessed high levels of soft skills and teaching self-efficacy. Skills such as lifelong learning, communication, emotional intelligence, intellectual and leadership significantly boosted their teaching self-efficacy. No significant differences were found in soft skills based on gender or age. The Department of Business and Social Sciences Education at the University of Cape Coast should integrate these soft skills into the teacher education curriculum. Teacher educators planning any training geared toward preservice teachers' soft skills should not discriminate gender and age.
xii,256p:, ill
Keywords: Geography Education; Hard Skills; Pre-service Teachers; Self-efficacy; Soft Skills; Teacher Educators